Slut-shaming and victim-blaming: a qualitative investigation of undergraduate students' perceptions of sexual violence. Issue 6 (2nd November 2017) - Hackman, Christine L.; Pember, Sarah E.; Wilkerson, Amanda H.; Burton, Wanda; Usdan, Stuart L.
Abstract: Sexual violence is a significant public health issue on US college campuses. This qualitative study aimed to better understand college student perceptions of sexual violence and bystander intervention. Gendered group and individual interviews were conducted with male ( n = 3) and female ( n = 12) undergraduates. Eight major themes emerged which included slut shaming; victim blaming; the preventive power of social networks; the importance of family influence and early education; ambiguous definitions of sexual behaviour and assault; perpetrator typology; and gendered actions. Sexual behaviour is simultaneously a topic of confusion and importance to college students. Future prevention efforts may be more relevant and efficacious by addressing the university experience and campus climate as perceived by the students.